Tinjauan Pustaka Penggunaan Gawai dengan Kejadian Miopia - Anugrahsari, Santi; Nugraha, Abraham William; Septrilla, Gladys; Veronica Agrippina (Jurnal MedScientiae, 2024)
Lifestyle changes during the pandemic has impacted the lives of almost every human being in the world. This lifestyle changes, especially the increase in the duration and frequency of gadget use for everyday routine can cause various unwanted side effects such as refractive disorders, especially myopia. This study aims to evaluate the correlation between gadget use and myopia and other relevant ocular biometric parameters such as axial length (AL) and spherical equivalent (SE). The literatures used in this study is taken from an electronic database using NCBI, ProQuest and Google Scholar with English keywords “Gadget”, “Myopia”, and “Vision Impairment” and in Indonesian “Gawai”, “Miopi”, dan “Kelainan Refraksi ”. The articles found was published between January 2012 and Juni 2022, which was then sorted according to the objective of this study and we found fifteen journals that we include in this study. The distance in which gadgets were used was found to have a correlation with myopia. Laying down while using gadgets was also found to be correlated with myopia. Meanwhile, the duration of gadget use has not been found to be correlated with myopia. Gadget use can be one of the risk factors for refractive disorders. Based on the literature we collected, it was found that gadget use distance less than 30 cm and laying down while using gadgets has a correlation with refractive disorders meanwhile the duration of gadget use was found to not be correlated with refractive disorders.